1978
DOI: 10.1302/0301-620x.60b4.711811
|View full text |Cite
|
Sign up to set email alerts
|

The uptake by the canine tibia of the bone-scanning agent 99mTc-MDP before and after an osteotomy

Abstract: The residue and extraction of technetium-labelled methylene diphosphonate (99mTc-MDP), a substance used in bone scanning, was examined in the canine tibia and found to be low. Examination of washout curves suggested that there were four compartments in cortical bone, a vascular, a perivascular, a bone fluid and a bone compartment. After an osteotomy in the canine tibia the residue of 99mTc-MDP increased. This was believed to be due to an increase in the blood supply to the bone and to an associated increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The relationship between blood flow and tracer uptake after a fracture has been examined in detail but there is still disagreement about whether the uptake is completely determined by increased flow or whether there are other factors involved [2][3][4]. One reason for this agreement appears to be that the relationship between flow and uptake is not necessarily constant.…”
mentioning
confidence: 99%
“…The relationship between blood flow and tracer uptake after a fracture has been examined in detail but there is still disagreement about whether the uptake is completely determined by increased flow or whether there are other factors involved [2][3][4]. One reason for this agreement appears to be that the relationship between flow and uptake is not necessarily constant.…”
mentioning
confidence: 99%
“…What has been observed is a peak in blood flow occurring between 7-14 days after fracture, followed by a prolonged remodeling period before a return to near pre-fracture flow rates. 2,3,4,5 These findings have correlated with innovatively designed studies investigating molecular angiogenic mediators and their relationship to endochondral fracture healing. The peak levels of these angiogenic mediators correlated with the peak rates of blood flow and were noted to coincide with the time of cartilage resorption, thus plausibly linking the two events.…”
Section: Introductionmentioning
confidence: 83%
“…injection (De Graaf 1980). This explanation can be disputed, however as it has been demonstrated that uptake of 99mTc-MDP in the canine tibia was equivalent when the radiopharmaceutical was injected as a bolus as well as in the form of a constant infusion over a 30-min period (Hughes et al 1978). …”
Section: Decreased Renal Function and Its Effect On The Scintigraphicmentioning
confidence: 99%